2017
DOI: 10.21699/ajcr.v8i5.628
|View full text |Cite
|
Sign up to set email alerts
|

Necrotizing Enterocolitis after Octreotide Treatment in a Preterm Newborn with Idiopathic Congenital Chylothorax

Abstract: Octreotide, a somatostatin analogue, has been used for the management of patients with refractory chylothorax. Side effects related to the gastrointestinal system associated with octreotide are necrotizing enterocolitis (NEC) and focal intestinal perforation. NEC is the most common and dangerous gastrointestinal emergency in premature infants. We present the development of necrotizing enterocolitis after octreotide treatment in a preterm infant with idiopathic congenital chylothorax which settled after discont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…Mohseni-Bod et al reported NEC development in term infant with coarctation of the aorta treated with octreotide for postoperative chylothorax 12. Buyuktiryaki et al described NEC development in a preterm infant with congenital chylothorax on day 4 of octreotide administration at 1 µg/kg/hour 13. Our’s is the third case of NEC report in infants treated for chylothorax using octreotide.…”
Section: Discussionmentioning
confidence: 77%
“…Mohseni-Bod et al reported NEC development in term infant with coarctation of the aorta treated with octreotide for postoperative chylothorax 12. Buyuktiryaki et al described NEC development in a preterm infant with congenital chylothorax on day 4 of octreotide administration at 1 µg/kg/hour 13. Our’s is the third case of NEC report in infants treated for chylothorax using octreotide.…”
Section: Discussionmentioning
confidence: 77%
“…Although octreotide is generally well tolerated, it can cause transient changes to blood glucose levels and gastrointestinal symptoms 36. Case reports have associated octreotide with necrotising enterocolitis (NEC) in term and preterm neonates treated for congenital chylothorax 37–39. Therefore, prior to treatment, the risks and benefits needs to be considered and during periods of octreotide treatment, patients should have their blood glucose levels and symptoms of NEC monitored closely.…”
Section: Discussionmentioning
confidence: 99%